An improved implicit split-step algorithm for dispersive band-limited FDTD applications - Ramadan, Omar (IEEE-Inst Electrical Electronics Engineers Inc, 2008)
An improved unconditionally stable envelope finite difference time domain (FDTD) algorithm is presented for modeling open region dispersive band-limited electromagnetic applications. The algorithm is based on incorporating the split-step implicit FDTD scheme into the stretched coordinates perfectly matched layer absorbing boundary conditions. Numerical examples carried out in 2-D domains are included to show the validity of the proposed formulations.
Keywords: dispersive media; envelope finite difference time domain (EFDTD); perfectly matched layer (PML); split-step